Sistem Kendali Suhu Mesin Tetas Telur Ayam Buras Menggunakan Kontroler PID dengan Metode Tuning Ziegler Nichols Open Loop Step Response - Agustian, Indra; Prakoso, Dian S; Faurina, Ruvita; Daratha, Novalio (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2022)
An egg incubator is a tool that helps the process of hatching eggs using an electric heater and is equipped with an egg rack that functions to evenly distribute the heat in the incubator. Good temperature control in the hatching process is something that greatly affects the hatching results. In this study, an egg incubator temperature control system was designed using the PID method with the Ziegler Nichols Open Loop Step Response tuning method. The control system is specifically for free-range chicken eggs which require a normal temperature of 37 °C-39 °C. The main control components are the microcontroller, the incandescent lamp heater, and the DHT22 temperature sensor. The open loop test shows a time delay of 20 seconds and a time constant of 385 seconds, so with the Ziegler Nichols open loop tuning method, the values of Kp = 23.1, Ki = 40, and Kd = 10. The test results show that the PID controller can control the temperature properly. In testing the hatching process within 21 days, the temperature control worked well, and the effect of changes in day and night temperature did not significantly affect the performance of the PID controller.